Urgensi komunikasi lintas budaya dalam organisasi di era globalisasi - Puspita, Ririnn Diyah (Maliki Interdisciplinary Journal, 2025)
In an era of globalization marked by increased international interaction and digitalization, cross-cultural communication has become a key aspect of organizational success in a multicultural environment. The main challenges faced include differences in values, norms, communication styles, language barriers, and stereotypes that can lead to misunderstandings and conflicts. To overcome these barriers, developing cultural competence and intelligence, including sensitivity and awareness of cultural contexts, is essential. Leaders with high levels of cultural intelligence can serve as effective bridges, helping to resolve conflicts and create inclusive and harmonious work environments. The use of digital technology supports cross-cultural communication, but it still requires awareness of cultural diversity to ensure that communication is not misinterpreted. Organizations that invest in intercultural training, build an open organizational culture, and strengthen leaders' ability to understand cultural diversity will gain a competitive advantage, enhance innovation, team cohesion, and achieve goals efficiently in an increasingly complex and diverse global market. Therefore, developing intercultural communication competencies is a key strategy for improving organizational performance and sustainability in the era of globalization.